A Review on Commercial Utility of Some Cultivable Algal Species Naturally Inhabiting in Water Bodies of Kota, Rajasthan - Vijayvargiya, Priyal; Shrivastava, Pratima (Journal for Research in Applied Sciences and Biotechnology, 2023)
Algae, not only one of the most significant organism of the planet, but also acclaimed as major photosynthetic autotrophs and responsibly contributing in sustainability of the planet by their unique yet significant ecological interactions. Along with production of biofuel and biomass, metabolic products of different species of algae are most commonly cultivated and used for pharmaceuticals, nutraceuticals, phytoremediation, wastewater treatment, antibiotics, dyes, food industry and so on. Apart from that, some members serve as bio indicator, provides specific information about the habitats they inhabit in, and thus serves as an effective tool for bio monitoring, and also helps in efficient management of the aquatic ecosystem. This study looks into the value of some naturally occurring chlorophycean and cyanophycean members which are intentionally cultivated and utilized at several parts of the world. For this study, samples were collected and identified for the presence of cultivable species of chlorophyceae and cyanophyceae, their known applications and commercial status so that further need of study for highest possibilities could be estimate in the field of algal cultivation for future prospective for aquatic algal habitats of Kota, Rajasthan.